Pendekatan Analisis Derau Putih untuk Arus Stokastik dari Gerak Brown Subfraksional - Herry Pribawanto Suryawan (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2022)
The subfractional Brownian motion is a Gaussian generalization of the Brownian motion whose increments are not stationary. In this paper we study the stochastic current of the one dimensional subfractional Brownian motion. For this purpose we use the method from white noise analysis by representing the subfractional Brownian motion as stochastic functionals of white noise. As the main result we prove that the stochastic current of the one dimensional subfractional Brownian motion is a generalized function in the space of Hida distributions.